Beta-agonist overuse and delay in obtaining medical review in high risk asthma: a secondary analysis of data from a randomised controlled trial - Janine Pilcher (Nature Portfolio, 2017)
Reliever inhaler overuse and delay in medical review in asthma In asthma, overuse of beta-agonist reliever medication and delay in seeking medical review in an exacerbation are linked to asthma deaths. Janine Pilcher at the Medical Research Institute of New Zealand, and co-workers, conducted a review of data from a study of 303 adult patients with severe asthma, followed over 24 weeks. The patients were allocated to either a budesonide/formoterol, or a salbutamol inhaler to take for symptom relief, in addition to their maintenance treatment. Inhalers were fitted with electronic monitors, to accurately document every use. In both groups, on 90% of days when an exacerbation requiring excess use of an inhaler occurred, patients did not follow-up with medical professionals within 48 h as advised. Further, in both groups, ‘extreme’ reliever inhaler use was recorded at least once in around one in four patients.